A study on hypertension management in patients on maintenance haemodialysis (International Journal of Biomedical Research, 2018)
A longitudinal study done on 50 CKD patients on maintenance haemodialysis on antihypertensive drugs. Hypertension in patients affected by CKD has been recognized as one of the major classical cardiovascular risk factors. The study aims to describe the class and number of drugs used for management of hypertension in patients on maintenance haemodialysis and to measure blood pressure and assess how many patients have achieved target blood pressure. On an average 42% of patients had adequate BP control and 58% were found not to have adequate BP control. The most commonly used antihypertensive BP medications being calcium channel blockers- amlodipine and alpha agonist clonidine followed by beta blockers- metoprolol and the most frequently used drug combination being amlodipine with clonidine. Weight reduction to achieve adequate dry weight for adequate BP control was found to be at range of 2-3kgs.